Impact of lowering the maximum speed limit of city roads on pedestrian traffic accident patients: A nationwide before-and-after study - Hun Gi Lee; Jung Ho Kim (PLoS ONE, 2025)
Traffic accidents (TAs) remain the leading cause of death globally; therefore, numerous efforts have been made to improve their occurrence and outcomes. Lowering the maximum road speed limit, named Safe Speed-5030, implemented in South Korea on April 17, 2021, is an example. This before-and-after study investigated the impact of this policy on pedestrian TA (P-TA) patients. We used the National Emergency Department Information System data for seven major cities in South Korea. We compared the characteristics of the patients who underwent P-TA and assessed the risks of emergency surgery, intensive care unit (ICU) admission, and unfavorable outcomes, using IBM SPSS version 21.0. The total number of patients who met with P-TAs was 26,842, with a 43.1% reduction from 17,105–9,737. A decrease was observed across all age groups; however, the rate was lower in the geriatric and severely injured groups. The proportions of emergency surgeries (46.5%), ICU admissions (36.5%), and unfavorable outcomes (21.5%) decreased. Nevertheless, this decrease was less pronounced in geriatric patients, and there was an increase in unfavorable outcomes among those in their 70s. After adjustment, the risk of emergency surgery did not show a statistically significant difference, but the risk of ICU admission and unfavorable outcomes increased. In conclusion, there was a significant reduction in the number of P-TA patients after the policy was implemented, but the effect was less pronounced in severely injured and geriatric patients. Considering these factors, we believe that Safe Speed-5030 had partly positive effects. Applying a suitably revised policy for specific group rather than completely scrapping it would be more appropriate.